Cluster randomised controlled trial on the effects of long-term home-based exercise for patients with chronic obstructive pulmonary disease with recent exacerbation: research protocol of the COPDtoParis Project - Ulla Møller Weinreich; Lars Pilegaard Thomsen; Jane Andreasen; Anna Lei Stoustrup; Thorvaldur S Palsson (BMJ Open Respiratory Research)
Background Chronic obstructive pulmonary disease (COPD) is a highly prevalent respiratory disease associated with significant health decline and economic burdens. Pulmonary rehabilitation is an effective intervention, but securing adherence to exercise is difficult, particularly for frail and disabled patients, challenged by leaving their home. Home-based exercise is an emerging alternative for persons with COPD, but long-term adherence is unclear. This study aims to investigate the effects, experiences and acceptability of long-term home-based cycling for patients with COPD post exacerbation.Methods and analyses This cluster randomised controlled trial will recruit hospitalised patients with COPD following hospitalisation following exacerbation of COPD. Participants will be referred to acute rehabilitation for 8 weeks at discharge. After rehabilitation, participants are randomised in clusters of five into 1 year of home-based cycling with the goal of cycling from Aalborg to Paris, or into the control group, who will receive standard care. Data will be collected at baseline, postrehabilitation/intervention initiation, at 6 and 12 months. Primary outcome is physical performance, while secondary outcomes include daily activity levels, lung function, mobility, frailty, symptom severity, health-related quality of life, survival rates and readmissions. A qualitative substudy will uncover experiences from participants. Daily activity levels will be measured using leg-mounted triaxial accelerometers. Other parameters will be tested with physical tests, questionnaires and interviews. The study aims to include 50 patients, with 25 participants in each group. A cost-effectiveness analysis will assess the impact on disease prevention and hospitalisation.Ethics and dissemination This study, approved by The North Denmark Region Committee on Health Research Ethics (N-20230008) and compliant with the Helsinki Declaration, includes annual safety and progress reporting of potential adverse events. Results will be disseminated through peer-reviewed publications, conference presentations and community outreach to ensure accessibility to participants, healthcare professionals and the public.Trial registration number NCT06235502 and Northern Jutland trial register (F2023-066).